THE EFFECT OF MUSIC THERAPY FOR PREGNANT WOMEN : A LITERATURE REVIEW - Aisyah Aisyah; Triana Sri Hardjanti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Psychological problems among pregnant women such as anxiety and depression potentially have an impact on the fetus and are associated with a risk of preeclampsia. One of therapy to decrease psychological problems during pregnancy is music therapy. The aim of this study was to identify and summarize the benefits of music therapy for decreased psychological problems among pregnant women.Methods: This was a literature review using several documents obtained from some databases, including Science Direct, Pubmed, Proquest, Taylor and Francis, Garuda Ristekdikti and Google Scholar. The literature search was conducted using keywords “music therapy in pregnant women” and literature published from 2008 to 2019 were selected. Results: Out of 263 published literature identified, only 10 were included in this literature review. The music therapy was observed with positive impacts on pregnant women. Music therapy serves as relaxation for pregnant women which helps reduce anxiety, depression, blood pressure, and psychological stress. Conclusion: Music therapy has several benefits for pregnant women’s health, particularly on reducing psychological problems and blood pressure.